2019
DOI: 10.1101/748079
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Developmental regulation of fear memories by an obesogenic high-saturated fat/high-sugar diet

Abstract: Background: Anxiety and stress-related disorders are strongly linked with obesity and the consumption of obesogenic diets. Paralleling clinical findings, we showed that the consumption of an obesogenic diet during adolescence disrupts the structural integrity of amygdalar and prefrontal cortex circuits underlying emotional responses to stress. These abnormalities were associated with a PTSD-like phenotype, including heightened stress reactivity to predator odor trauma, anxietylike behaviors, and profound learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 115 publications
(149 reference statements)
2
5
0
Order By: Relevance
“…We have modeled this relationship by measuring stress reactivity to traumatic stress in a rat model of diet-induced obesity (DIO). Consistent with studies in obese adolescents, we reported that adolescent diet-induced obesity (DIO) in rats: 1) reduces hippocampal volume [12], 2) impairs the maturation of the corticolimbic fear circuits [13], 3) enhances behavioral vulnerabilities to psychosocial stress [12][13][14], and 4) results in profound fear extinction learning deficits [13,14], even in the absence of an obesogenic phenotype [15].…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…We have modeled this relationship by measuring stress reactivity to traumatic stress in a rat model of diet-induced obesity (DIO). Consistent with studies in obese adolescents, we reported that adolescent diet-induced obesity (DIO) in rats: 1) reduces hippocampal volume [12], 2) impairs the maturation of the corticolimbic fear circuits [13], 3) enhances behavioral vulnerabilities to psychosocial stress [12][13][14], and 4) results in profound fear extinction learning deficits [13,14], even in the absence of an obesogenic phenotype [15].…”
Section: Introductionsupporting
confidence: 68%
“…Obesity is highly comorbid with anxiety and stress-related disorders. Our studies indicate that consumption of an obesogenic WD during adolescence heightens stress reactivity, promotes anxiety-like behaviors, and impairs the structural integrity of neural substrates implicated in stress-induced psychopathology in rats [12][13][14][15]. Furthermore, there is support to the notion that impairments in brain and behavior can occur even in the absence of an obesogenic phenotype [13,[57][58][59][60][61][62][63]].…”
Section: Obesogenic Diets Trigger Redox Dysregulation and Neuroinflammentioning
confidence: 60%
See 1 more Smart Citation
“…Control diet choice can thus conceivably confound data interpretation and affect reproducibility. Given that initially both the CHOW and CD groups had identical biometric and behavioral outcomes, we opted to use the more appropriate CD group as control for the WD group (Vega-Torres et al, 2019). The macronutrient composition and fatty acid profiles are detailed in Table 1.…”
Section: Dietsmentioning
confidence: 99%
“…We would like to thank the staff at the animal care facility. This manuscript has been released as a preprint in bioRxiv ( Vega-Torres et al, 2020 ) as a significantly revised manuscript from another preprint listed in the same repository ( Vega-Torres et al, 2019 ).…”
mentioning
confidence: 99%